Polysemy in Economic News about Inflation and Import Restrictions on CNN Arabic - Khoizuronah, Sayyidah; Latif , Muwaafiquddin Abdul; Athoillah, Wildan Falah (Journal of Arabic Language Studies and Teaching, 2023)
This research aims to reveal, understand, and analyze words containing polysemy in economic news about inflation and import restrictions on CNN Arabic so that everything is correct in understanding the news. The object of this research is two news stories about the economy on CNN Arabic. This research was conducted using a qualitative descriptive method: collecting, analyzing, and describing data. The research results showed that twenty-four words containing polysemy were found in economic news on CNN Arabic. It includes polysemy of nouns, verbs, and adjectives, with details of thirteen noun words, seven verb words, and four adjective words. The factors causing polysemy in economic news are shifts in sentence usage and structure and the influence of foreign languages. Most of the meanings of polysemy in economic news on CNN Arabic are metaphors of lexical meaning, and these words can be known by looking at a dictionary or analyzing sentence structure.